Integração do Balanced Scorecard e modelo de Slack com ênfase na gestão do desempenho organizacional para o ramo de telecomunicações - Santos, Lucas Almeida dos (2016)
In the current climate of economic environment, organizations need to direct their efforts to maximize the effectiveness of your Organizational Management. Thus, the use of tools and performance indicators, such as the Balanced Scorecard (BSC) and Slack model guide the organization through perspectives that align the company's shares to their strategies, allowing thus the performance evaluation and guiding the Organizational Management. In this context, the present study is guided by the integration of the BSC and Slack model. Because in the age of technology and information, a battle is fought in the consumer market, forcing companies to deliver their products and more quickly and with quality services. The weather this sector dictate rules for how Authorized Agents (representatives) should behave on the market, making complex management process when it comes to expanding their business and strategize long term. In this sense, the research is presented as a case study with a qualitative and quantitative approach than the use of Fuzzy Delphi method as a way of indicators panel validation, developed from the variables of the models with the mirror reality by branch Telecommunications. As a result of this integration, will offer one-Performance Indicators Panel for the Telecommunications industry, with the emphasis on Organizational Management. As result of this integration, there is the creation of a Performance Indicator Panel for the Telecommunications branch, with the emphasis on Organizational Management. The transformation of the responses obtained in NTFs possible to reduce the inaccuracies and pointed out that the perceptions of managers regarding the level of importance on indicators approached the membership function (3.0, 4.0, 5.0), so, for term 4 Very Important. The elimination of the indicators with Gi <3.35 did not influence the proposed panel, as due to its Gi (sum), belonged to the degrees of No Importance (SI) Somewhat Important (PI) and indifferent (I). Finally, it highlights the relevance of this study for the academic community and for the participating organization and the Telecommunications branch